KAJIAN EXPERIMEN KEKUATAN TARIK MATERIAL KOMPOSIT SERAT BAMBU DAN PASIR BESI DENGAN SUSUNAN SERAT HORIZONTAL DENGAN MENGGUNAKAN METODE HAND LAY UP - al mahdi pinem; Fery Setiawan; Edy Sofyan (Sekolah Tinggi Teknologi Kedirgantaraan, 2023)
Composite is a material formed from a combination of two or more constituent materials through homogeneous mixing. Where the mechanical properties of each of the constituent materials are different. Composite material is also a very important material because it has special properties, these properties include its stiffness, strength, non-corrosion and fatigue life which is better than other conventional materials. The purpose of this study is to determine the mechanical characteristics of Composite materials. bamboo fiber and iron sand on weight variations, the best mechanical properties characteristics of several variations and determine voids or bubbles in the resin. The process of making this bamboo fiber Composite material uses volume variations of bamboo fiber by 15%, 25% and 35% then followed by printing the material on the astm d369-90 tensile test mold. In the tensile testing process, the highest mechanical properties were found in the High variation with a tensile strength value of 2.70 kgf/mm2, and a strain of 0.51% of the initial size. While the lowest mechanical properties are found in the Low variation with a tensile strength value of 2.16 kgf/mm2 and a strain of 0.33% of the initial size.